Snack Portion Sizes for Preschool Children Are Predicted by Caregiver Portion Size, Caregiver Feeding Practices and Children′s Eating Traits - Reale, Sophie (Nutrients, 2019)
Caregivers are mostly responsible for the foods young children consume; however, it is unknown how caregivers determine what portion sizes to serve. This study examined factors which predict smaller or larger than recommended snack portion sizes in an online survey. Caregivers of children aged 2 to 4 years were presented with 10 snack images, each photographed in six portion sizes. Caregivers (n = 659) selected the portion they would usually serve themselves and their child for an afternoon snack. Information on child eating traits, parental feeding practices and demographics were provided by caregivers. Most caregivers selected portions in line with recommended amounts for preschool children, demonstrating their ability to match portion sizes to their child′s energy requirements. However, 16% of caregivers selected smaller than recommended low energy-dense (LED, e.g., fruits and vegetables) snacks for their child which was associated with smaller caregiver′s own portion size, reduced child food liking and increased satiety responsiveness. In contrast, 28% of caregivers selected larger than recommended amounts of high energy-dense (HED, e.g., cookies, crisps) snacks for their child which were associated with larger caregiver′s own portion size, greater frequency of consumption, higher child body mass index (BMI), greater pressure to eat and lower child food liking. These findings suggest that most caregivers in this study select portions adjusted to suit their child′s age and stage of development. Future interventions could provide support to caregivers regarding the energy and nutrient density of foods given the relatively small portion sizes of LED and large portions of HED snacks offered to some children.